Legal Consequences and Supervision of Violations of the Notary Code of Ethics in Promotion of Positions on Social Media - Maulani, Lora Purnama (Riwayat: Educational Journal of History and Humanities, 2025)
A notary is a general official who is authorized to make deeds and has other authority as referred to in the Notary Position Law. Notaries in carrying out their positions are guided by the Notary Code of Ethics and the Notary Position Law. Article 4 paragraph (3) of the Notary Code of Ethics prohibits Notaries from promoting themselves on social media, but in practice there are still violations of this. The purpose of this study is to analyze and examine the legal consequences of violations of the Notary Code of Ethics related to promotion of positions on social media and to understand and conclude the form of supervision carried out by the Notary Honorary Council on these violations. The research method used in this study is the normative juridical method by obtaining data from literature studies and field studies. The results of this study can be concluded that the Notary Honorary Council and the Regional Honorary Council in carrying out their supervisory functions are obliged to hold the Notary concerned accountable by imposing appropriate sanctions firmly, either in the form of civil sanctions, administrative sanctions, code of ethics sanctions and even criminal sanctions. The form of supervision that can be carried out by the Notary Honorary Council is through regular and continuous coaching and briefing to Notaries so that they remain obedient and comply with the code of ethics and the UUJN in carrying out their positions.